IMPLEMENTASI PERATURAN KEPOLISIAN NEGARA REPUBLIK INDONESIA NOMOR 8 TAHUN 2021 TENTANG PENANGANAN TINDAK PIDANA BERDASARKAN KEADILAN RESTORATIF - Nur'aini Jamal (JOURNAL EQUITABLE, 2023)
In article 16 and Article 18 of UU Kepolisian Nomor 2 Tahun 2002 concerning the Indonesia National Police, The National Police have formulated a new concept to enforce criminal law that accommodates the norm and values prevailing in societyas a solution as well as providing legal certainty, especially fot the benefit of society’s sense of justice. The approach to providing legal certainty by applying the handling of criminal acts based on restorative justice is the settlement of criminal acts by involving the perpetrator, victim, perpetrator’s family, victim’s family, community leaders, religious leaders, traditional leaders, or stakeholders to jointlyseek a fair settlement through by emphasizing restoration to its original state. A form of mediation called Restorative is to repair losses caused by crimes involving victims, to see the perpetrator’s accountability, and prevent similar failures from occurring in the future. Restorative is a legal umbrella to describe programs that can see criminal acts and respond with a restorative perspective.